Ian Hacking’s metahistory of science - Simos, M.; Arabatzis, T. (Philosophical Inquiries, 2021)
In this paper we attempt a critical appraisal of the relation between history of science and philosophy of science in Ian Hacking’s styles of scientific reasoning project. In our analysis, we employ a distinction between “historical philosophy of science” and “philosophical history of science”: the former aims at addressing philosophical issues, while the latter aims at telling stories about the scientific past that are informed by philosophical considerations. We argue that Hacking practices historical philosophy of science; discuss how his approach is differentiated from the so-called confrontation model; and show that he opts for a strong integration between history and philosophy of science. Finally, we discuss the historiographical implications of his approach and suggest that his aim to maintain a middle position, on the one hand, between contingency and inevitabilism, and, on the other, between internalism and externalism in the explanation of the stability of scientific knowledge, is compromised by his philosophical commitments.